A Stylistic Analysis of Selected Representative Samples of Claire Allan’s (2018) Her Name Was Rose - Marwa Nawzad Rashid; Saza Ahmed Fakhry Abdulla (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
This paper discusses the stylistic analysis of Claire Allan’s (2018) Her Name Was Rose. For the theoretical framework, certain analytical approaches to stylistic analysis have been introduced in regards to lexical, grammatical categories, figurative language, as well as some textual features. The stylistic categories proposed by Leech and Short (2007) have been used for the examination of the stylistic features of Allan’s fictional portrayal of Emily who is the narrator of the novel. Since stylistics examines both literary and non-literary texts, this work examines the stylistic features in an Irish novel. In the novel, some representative samples have been taken from chapter one, three and four to identify the stylistic features. The findings show that Allan uses certain linguistic deviation in the selection of some of the lexical categories that expresses the narrator’s deep feeling through the uses of lexical deviation to create a sense of ambiguity that brings an aesthetic value of the text. At the same time, Allan also tends to foreground the normal usage of some sentence structures through using repetition of some lexical and grammatical categories. Furthermore, Allan uses an effective technique to describe the event of the novel by evoking moods, generating suspense, as well as preparing the readers for expecting what will happen in the rest of the novel.